INTERIOR DESIGNERS IN SOCIETY 5.0, MACHINE UTILIZATION IN MAKING INTERIOR WORK EASIER - Atmadi, Tunjung (UPT Pusat Penerbitan LP2MPP ISI Bali, 2024)
Society 5.0 is a concept that allows humanity to use modern technology-based science such as machines to meet needs and make human life easier, especially for interior designers of interior work. The presence of society 5.0 has made a major contribution to interior designers. The purpose of this study is the existence of a technology-based machine learning innovation that makes it easier for designers to work on designer work methods, designer communication methods and work methods in workshops without regard to space, time and place. Through a case study approach, with qualitative descriptive analysis, the role of interior designers in the era of society 5.0 can be understood. An interior designer not only works and masters computers as a medium for designing his designs, but must master and operate supporting machine tools in realizing his ideas. In addition, interior designers must also apply the concept of sustainability design as a sustainable development goal, which is very concerned with environmentally friendly design.